Trajetória social de alunos de um curso pré-vestibular popular - Suficier, Darbi Masson [UNESP]; Muzzeti, Luci Regina [UNESP]; Reina, Fabio Tadeu (My University, 2013)
The aim of the research that originated this article was the analysis of the social trajectory of students from a public preparatory course and the verification of their expectations about higher education. Data collection was based on a questionnaire with open and closed-ended questions and a semi-structured interview, based on the models used by Muzzetti (1997). Data were analyzed by the elaboration of thematic charts. Based on the researches conducted by Pierre Bourdieu (1997, 2007), this research concluded that the students understand that schooling is, besides being a viable alternative in the search for social ascension, the redeeming of social ills. Profession choice based on natural talent or divine gift generate expectations which attest the lack of knowledge about the school system by students and their parents, which is reinforced by the belief in opportunity equality.

O objetivo da pesquisa que originou este artigo foi analisar a trajetória social de alunos e alunas de um curso pré-vestibular popular e verificar suas expectativas sobre o Ensino Superior. Foram utilizados na coleta dos dados questionário com questões abertas e fechadas e entrevista semiestruturada, elaborados com base nos modelos utilizados por Muzzeti (1997). Os dados foram analisados a partir da elaboração de quadros temáticos. Apoiada nas pesquisas realizadas por Pierre Bourdieu (1997, 2007), essa pesquisa concluiu que os estudantes entendem que a escolarização é, além de uma alternativa viável na busca pela ascensão social, a redentora dos males sociais. A escolha da profissão pela crença no talento natural ou por um dom divino gera expectativas que atestam o desconhecimento do sistema de ensino pelos estudantes e por seus pais, o que é reforçado pela crença na igualdade de oportunidades.
Social trajectory of students from a free preparatory course for selection to university
Keywords: Social trajectory; Public preparatory course; Habitus; Trajetória Social; Curso pre-vestibular popular; Habitus